2017
DOI: 10.1016/j.autrev.2017.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis in the real world: A systematic review of fingolimod as a case study

Abstract: The included studies provide good evidence of the real-world effectiveness of fingolimod and highlight the diversity of methodologies used to assess treatment benefit in clinical practice. Future studies could address the evidence gaps found in the literature and the challenges associated with researching MS when designing real-world studies, assessing data, and comparing evidence across studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 52 publications
2
39
1
2
Order By: Relevance
“…The majority of patients also achieved a long‐term stabilization of EDSS, supporting the findings from clinical trials and other long‐term observational clinical studies . In addition, treatment‐naïve patients showed a significant improvement of their EDSS, probably reflecting a recovery from the relapse that motivated fingolimod start and the larger compensatory capacity known to characterize younger patients .…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The majority of patients also achieved a long‐term stabilization of EDSS, supporting the findings from clinical trials and other long‐term observational clinical studies . In addition, treatment‐naïve patients showed a significant improvement of their EDSS, probably reflecting a recovery from the relapse that motivated fingolimod start and the larger compensatory capacity known to characterize younger patients .…”
Section: Discussionsupporting
confidence: 78%
“…In comparison to other real-world studies, the mean treatment duration of 32 months in our study is relatively long, and the retention rates, e.g. 95.7% at 24 months and 87.8% at 36 months, are mostly higher than previously reported treatment retention rates for fingolimod under real-life conditions (reviewed by Ziemssen et al [8]). For instance, in other real-world studies, Alroughani et al [10] showed a fingolimod discontinuation rate of 5.3% after a mean treatment duration of 18.5 months, whereas Yamout et al saw a discontinuation rate of 28.7% after a mean treatment duration of 19.2 months [9].…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…These initial data propelled us to further study the involvement of IL37 in MS. To do so, we evaluated in silico expression and circulating levels of IL37 in patients with different forms of the disease and also upon treatment with different disease modifying drugs [37]. The combined interpretation of the resulting data strengthens and extends the current emerging concept that endogenous IL37 plays an important role in determining onset and progression of MS.…”
Section: Introductionmentioning
confidence: 89%